2014
DOI: 10.1007/978-3-319-04220-6_1
|View full text |Cite
|
Sign up to set email alerts
|

Host Impairments in Patients with Neoplastic Diseases

Abstract: Healthy individuals possess an immune system comprising physical barriers, innate and acquired immunity as well as the indigenous microflora that populate the body surfaces. The immune system maintains constant vigilance over the body at the cellular level as well as at the interface between the host integument and the resident microflora. However, neoplastic diseases and their treatment often lead to impaired immunity resulting in an increased risk of infections due to viruses, bacteria, fungi, and protozoa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 174 publications
0
10
0
Order By: Relevance
“…Infections are a significant cause of morbidity and treatment-related complications among patients with cancer and may develop as a consequence of neutropenia from aggressive chemotherapeutic regimens, exposure to invasive procedures or medical devices, hematopoietic stem cell transplantation (HSCT), malnutrition, and/or effects of the malignancy itself on immune function. 23,24 The exceptionally high SMR for infectious disease mortality associated with NHL in our analyses is undoubtedly a reflection of its relation with HIV infection, particularly given the period spanned by our study. However, even when patients with NHL were excluded, the SMRs remained significantly elevated among all other AYAs with cancer combined.…”
Section: Discussionmentioning
confidence: 92%
“…Infections are a significant cause of morbidity and treatment-related complications among patients with cancer and may develop as a consequence of neutropenia from aggressive chemotherapeutic regimens, exposure to invasive procedures or medical devices, hematopoietic stem cell transplantation (HSCT), malnutrition, and/or effects of the malignancy itself on immune function. 23,24 The exceptionally high SMR for infectious disease mortality associated with NHL in our analyses is undoubtedly a reflection of its relation with HIV infection, particularly given the period spanned by our study. However, even when patients with NHL were excluded, the SMRs remained significantly elevated among all other AYAs with cancer combined.…”
Section: Discussionmentioning
confidence: 92%
“…Herein, we found that the risk of dying from infections in cancer patients was three times higher than that of the cancer-free population. Previous studies have interpreted the high morbidity and mortality of infections as a consequence of the immunosuppression induced by effects of malignancy itself and many systematic cancer therapies, including chemotherapeutic regimens, hematopoietic stem cell transplantation (HSCT), invasive procedures or medical devices and malnutrition [7,22,23]. For instance, chemotherapy is frequently recommended by clinicians to treat cancer patients because of its proved therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CRC has a particularly increased mortality rate from infectious diseases. As a predominant cause of death among patients with cancer, fatal infections have been interpreted to be a consequence of the immunosuppression induced by the malignancy itself and by various modern cancer therapies, including chemotherapeutic regimens, invasive procedures, or medical devices and malnutrition [ 44 46 ]. Neutropenia-related infection has been shown to be a common side effect of chemotherapy and can result in sepsis [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%